2005
DOI: 10.1002/ijc.20871
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 induces transcriptional activation of vascular endothelial growth factor (VEGF) in astrocytes in vivo and regulates VEGF promoter activity in glioblastoma cells via direct interaction between STAT3 and Sp1

Abstract: Interleukin-6 (IL-6) expression is strongly correlated with the degree of human glioma malignancy and necessary for tumor formation in a mouse model of spontaneous astrocytomas. Yet, exactly how IL-6 contributes to malignant progression of these brain tumors is still unclear. We have scrutinized the mechanism of transcriptional activation of vascular endothelial growth factor (VEGF) expression by IL-6 in the mouse brain and in glioblastoma cells. We demonstrate here that IL-6 drives transcriptional upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
136
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 48 publications
17
136
0
1
Order By: Relevance
“…3D). In agreement, IL6 has been shown to promote angiogenesis (Cohen et al 1996;Wei et al 2003;Huang et al 2004;Loeffler et al 2005;Nilsson et al 2005). However, endothelial cells typically do not express detectable levels of IL6R ( Supplementary Fig.…”
Section: Ras-induced Il6 Secretion Acts In a Paracrine Fashion To Prosupporting
confidence: 62%
“…3D). In agreement, IL6 has been shown to promote angiogenesis (Cohen et al 1996;Wei et al 2003;Huang et al 2004;Loeffler et al 2005;Nilsson et al 2005). However, endothelial cells typically do not express detectable levels of IL6R ( Supplementary Fig.…”
Section: Ras-induced Il6 Secretion Acts In a Paracrine Fashion To Prosupporting
confidence: 62%
“…[52][53][54] In this context, it is interesting to note that, in the present study, there was no increase in the amount of tumor necrosis in the MT-ret ϩ/Ϫ mice lacking IL-6. This observation suggests that blood supply to these tumors was not critically impaired because of the lack of IL-6.…”
Section: Discussionmentioning
confidence: 76%
“…Although previous studies have confirmed that IL-6 is important in both physiological and pathological angiogenesis (Cohen et al, 1996;Mahnke et al, 2000), IL-6 has recently received more attention as a critical cytokine implicated in the angiogenesis of several human cancers, including cervical cancer, basal cell carcinoma, glioma, gastric carcinoma and mesothelioma (Wei et al, 2003;Huang et al, 2004;Jee et al, 2004;Loeffler et al, 2005;Adachi et al, 2006;Saidi et al, 2009). Strikingly, these investigations provide evidence that IL-6 may promote VEGF-induced tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…siRNA-mediated targeting of IL-6 in vector or ILK-overexpressing cells inhibited the levels of phosphorylated STAT3 (Figure 6a). Because IL-6 is reported to upregulate VEGF to induce angiogenesis (Wei et al, 2003;Huang et al, 2004;Loeffler et al, 2005;Adachi et al, 2006), we used VEGF antibody to assay for differences in VEGF protein levels between the vector and ILK-overexpressing MMRU, and SK-mel-3 cells knocked down for IL-6 and STAT3 proteins. Control siRNA-transfected ILK-overexpressing melanoma cells exhibited a 1.4-to 1.5-fold increase in VEGF protein compared with the vector cells (Figure 6a).…”
Section: Ilk Expression In Melanoma Cells Induces Il-6-dependent Angimentioning
confidence: 99%